A critical review and update on autoimmune encephalitis: understanding the alphabet soup - Simabukuro, Mateus Mistieri; Silva, Guilherme Diogo da; Castro, Luiz Henrique Martins; Lucato, Leandro Tavares (Arquivos de Neuro-Psiquiatria, 2022)
Autoimmune encephalitis (AE) comprises a group of diseases mediated by antibodies against neuronal cell surface or synaptic antigens, such as ion channels or neurotransmitter receptors. New clinical syndromes and their associated antibodies were and are still being characterized over the last two decades. The fact that their main clinical features are interdisciplinary, - encompassing neuropsychiatric symptoms, cognitive dysfunction, epileptic seizures, movement and sleep disorders - has led to a surge of interest in this field. Some of these diseases present with a well-defined syndrome, being recognizable on clinical grounds. Correct diagnosis is important since AE are potentially treatable diseases, despite their severity. On the other hand, an increasing number of neuronal antibodies being described casts doubt upon the way we should utilize antibody testing and interpret results. In this article we review, summarize and update the current knowledge on antibody mediated encephalitis.
Keywords: Encephalitis; Anti-N-Methyl-D-Aspartate Receptor Encephalitis; Limbic Encephalitis; Paraneoplastic Syndromes, Nervous System.